An Pengaruh Perlakuan Dekolorisasi Karbon Aktif terhadap Intensitas Warna dan Kadar Fenolik Total dari Ekstrak Daun Okra (Abelmoschus esculentus L.) - Syumillah Saepudin; Kusdi Hartono; Annisa Khoerunnisa; Nurul Rahmayanti; Raihani Febriani (Journal of Pharmaceutical and Sciences, 2026)
Background: Okra leaves (Abelmoschus esculentus L.) are a potential natural source of phenolic compounds with antioxidant activity and prospective applications in pharmaceutical and cosmetic formulations. However, the dark green color of the extract, mainly due to chlorophyll pigments, may negatively affect the aesthetic quality of the final product. Decolorization using activated carbon is therefore required to improve visual appearance without reducing bioactive compounds. Objective: This study aimed to evaluate the effect of activated carbon decolorization on color intensity and total phenolic content of okra leaf extract. Methods: Okra leaf extract was prepared by maceration using 70% ethanol. Decolorization was performed using activated carbon at various concentrations (0.5–8%) and contact times (2–72 hours). Color intensity was measured using a UV–Vis spectrophotometer at 663.50 nm. Total phenolic content was determined using the Folin–Ciocalteu method and expressed as mg gallic acid equivalent (GAE)/g extract. Statistical analysis was conducted using one-way ANOVA at a significance level of 0.05. Results: Activated carbon effectively reduced color intensity through adsorption mechanisms. Variation in activated carbon concentration did not significantly affect total phenolic content (p = 0.71), whereas contact time had a significant effect (p = 0.0014). The optimum condition was observed at 24 hours of contact time, showing reduced color intensity while maintaining phenolic content. No significant correlation was found between absorbance reduction and total phenolic content (ρ = 0.102; p = 0.555), indicating selective adsorption. Conclusion: Activated carbon decolorization effectively improves the visual appearance of okra leaf extract without significantly reducing its total phenolic content. The optimum contact time was 24 hours, suggesting its potential application in enhancing the quality of natural-based pharmaceutical and cosmetic preparations.